A new species of the genus Paranataretus El-Sonbati, 2023 (Hemiptera: Cicadellidae: Deltocephalinae) from the continental Africa - Gnezdilov, Vladimir M. (Zootaxa, 2023)
A new species of the leafhopper genus Paranataretus El-Sonbati, 2023, P. albertinus sp. n., is described from North Kivu Province of the Democratic Republic of Congo which is first record of the genus from Africa. New records from Madagascar is given for Paranataretus brevis (Gnezdilov, 2020). Relationships of the species within the genus Paranataretus are discussed.